Cyber Resilience of Autonomous Mobility Systems : Cyber Attacks and Resilience-Enhancing Strategies - Zou, Bo (World Bank, Washington, DC, 2020)
The increasing cyber connectivity of vehicles and between vehicles and infrastructure will drastically reshape mobility in the coming decades. Although the advent of connected mobility is expected to benefit travelers and society by smoothing traffic, improving rider convenience, and reducing accidents, the augmented cyber components in connected and autonomous vehicles and related infrastructure also give rise to cyber attacks on the transportation system. Yet, little attention has been paid to transportation cyber resilience. This paper thus proposes an investigation on this topic with a comprehensive literature review. Cyber components and plausible autonomous mobility systems operation scenarios are discussed, before identifying possible cyber attacks to autonomous mobility systems at the vehicle and system levels. The discussion then moves to existing practices to enhance cybersecurity, and several strategies are investigated toward enhancing autonomous mobility system cyber resilience. At the vehicle level, creating layers and separation to reduce cyber component connectivity and deploying an independent procedure for data collection and processing are important in vehicle design and manufacturing. At the system level, recommended strategies include keeping redundancy in transportation capacity, maintaining a separate road network, and deploying different sub-autonomous mobility systems.